(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Among all the crimes, sex related crimes are the most heinous and humiliating. Objective: The aim of our study was to ascertain incidence of sexual violence in Lahore and to analyze the data with respect to epidemiological and demographic characteristics, relationship between victim and assailant, time of reporting of cases, pattern of physical injuries and evidence collection from victims of sexual violence. Material and Method: This retrospective study was conducted on 27 cases of sexual assault brought to Forensic Medicine Department of King Edward Medical University, Lahore from January 2012 to December 2013 for medicolegal examination. Details pertaining to age, sex, religion, socioeconomic status, site of incident, time interval between incidence and medical examination, number of assailants, relationship with assailants, findings of genital examination and results of evidence collected were noted. Data was analyzed using SPSS version 20. Result: Out of 27 victims of sexual assault, (81.4%) were females and (18.5%) were males. All victims of sodomy were males. The most affected age group was 10-19 years (62.9 %). Majority of the victims were unmarried (59.2%) and students (55.55%). The highest number of victims was examined on the first and second day (22.22% each). Gang rape was seen in 37% cases. The vast majority of the victims knew the assailant (44.4%). External injuries were seen in 5 cases (18.51%). Hymen was intact in 2 victims (9.09%). The tears of hymen were old in 12 victims (54.54%) while they were fresh in 8 victims (36.36%) out of 20 cases of ruptured hymen. Tear of anal mucous membrane was seen in 3 victims of sodomy (11.11%). Semen was detected in 7cases (26.92%). Conclusion: The study highlights the importance of addressing rape as an important health issue.